Formulation of Policy for Cyber Crime in Criminal Law Revision Concept of Bill Book of Criminal Law (A New Penal Code) - Eko Soponyono; Brav Deva Bernadhi (Proceeding of the Electrical Engineering Computer Science and Informatics, 2016)
Development of national legal systems is aimed to establish the public welfare and the protection of the public. Many attempts has been carried out to renew material criminal law and those efforts results in the formulation of the concept of the draft Law Book of the Law of Criminal Law in the form of concept criminal code draft. The basic ideas in drafting rules and regulation based on the values inside the idology of Pancasila are balance among various norm and rules in society. The design concept of the New Criminal Code Act is anticipatory and proactive to formulate provisions on Crime in Cyberspace and Crime on Information and Electronic Transactions. Several issues compiled in this paper are whether the policy in formulation of cyber crime is embodied in the provisions of the current legislation and what the policies formulation of cyber crime is in the concept of the bill book of law - criminal law recently?.